2021
DOI: 10.1038/s42004-021-00559-2
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-fed reversible protonic ceramic fuel cells with Ru-based catalyst

Abstract: The intermediate operating temperatures (~400–600 °C) of reversible protonic ceramic fuel cells (RePCFC) permit the potential use of ammonia as a carbon-neutral high energy density fuel and energy storage medium. Here we show fabrication of anode-supported RePCFC with an ultra-dense (~100%) and thin (4 μm) protonic ceramic electrolyte layer. When coupled to a novel Ru-(BaO)2(CaO)(Al2O3) (Ru-B2CA) reversible ammonia catalyst, maximum fuel-cell power generation reaches 877 mW cm−2 at 650 °C under ammonia fuel. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…[4,5,7] However, increasing the current density cannot continuously increase the ammonia production rate. [17] Therefore, it is essential to operate PCECs under an optimal current density to obtain high ammonia yield and energy efficiency. As shown in Figure 7, at a relatively low current density, the negative electrode is covered with sufficient chemisorbed nitrogen that will be readily reduced by hydrogen/proton.…”
Section: Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5,7] However, increasing the current density cannot continuously increase the ammonia production rate. [17] Therefore, it is essential to operate PCECs under an optimal current density to obtain high ammonia yield and energy efficiency. As shown in Figure 7, at a relatively low current density, the negative electrode is covered with sufficient chemisorbed nitrogen that will be readily reduced by hydrogen/proton.…”
Section: Operating Conditionsmentioning
confidence: 99%
“…Numerous lab-scale PCECs have been demonstrated to realize these applications. [5,14,17,23,28] These previous studies have centered on proving the concept of producing chemicals in PCECs. However, the reaction thermodynamics, energy efficiency, potential reaction mechanisms, critical barriers, and potential strategies to overcome the challenges are not discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…49 Zhu et al reported ammonia-fed reversible protonic ceramic fuel cells with a Ru-based catalyst. 52 operating for 1250 h; however, ammonia was cracked in a separate reactor. When the button cell was operated under direct ammonia, the voltage dropped in 15 h. He et al utilised a Pd added electrolyte to produce 0.724 W cm −2 at 650 °C with direct ammonia feed.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Among them, reversible protonic ceramic cells (RPCCs) based on proton-conducting electrolytes at intermediate temperatures (IT < 700 °C) have various advantages in terms of energy efficiency, durability, and cost, compared to the low-temperature water-splitting unitized reversible fuel cells (URFCs) and high-temperature reversible solid oxide cells (RSOCs). [4][5][6] RPCCs can Despite their high electrocatalytic activity for oxygen electrode reactions, the low phase stability and high thermal expansion of perovskite structured materials have created difficulties in cell fabrication scale-up and long-term operational stability of reversible ceramic cells. Herein, an exceptionally high-performance electrocatalyst is presented based on a misfit-layered structure, Na 0.15 Ca 2.85 Co 4 O 9-δ (NCCO).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,3 ] Among them, reversible protonic ceramic cells (RPCCs) based on proton‐conducting electrolytes at intermediate temperatures (IT < 700 °C) have various advantages in terms of energy efficiency, durability, and cost, compared to the low‐temperature water‐splitting unitized reversible fuel cells (URFCs) and high‐temperature reversible solid oxide cells (RSOCs). [ 4–6 ] RPCCs can not only generate high power density, including high CH 4 conversion and carbon coking resistance, but also directly produce high‐purity H 2 without additional equipment and the problem of Ni‐cermet fuel electrode decomposition. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%